Reduction of corpus callosum activity during whisking leads to interhemispheric decorrelation - Yael Oran (Nature Portfolio, 2021)
Interhemispheric correlations are mediated by the corpus callosum, an extensive fiber bundle connecting the cortical hemispheres. The authors show that interhemispheric correlations between the somatosensory cortices of awake mice are reduced during whisking as a result of lower callosal activity.